Gendered work-family life courses and financial well-being in retirement - Ignacio Madero-Cabib; Anette Eva Fasang (Advances in Life Course Research, 2016)
How are gendered work–family life courses associated with financial well-being in retirement? In this article we compare the cohorts born 1920–1950 in West Germany and Switzerland, whose adult life courses are characterized by similar strong male-breadwinner contexts in both countries. The countries differ in that Switzerland represented a liberal pension system, whereas Germany represented a corporatist protective pension system when these cohorts retired. We therefore assess how gendered work–family life courses that developed in similar male-breadwinner contexts are related to financial well-being in retirement in different pension systems. Using data from the SHARELIFE survey we conduct multichannel sequence analysis and cluster analysis to identify groups of typical work–family life courses from ages 20 to 59. Regression models estimate how these groups are associated with the individual pension income and household income in retirement. Results show that women who combined motherhood with part time work and extended periods out of the labour force have even lower individual pension income in Switzerland compared to their German peers. This relative disadvantage partly extends to lower household income in retirement. Findings support that male breadwinner policies earlier in life combined with liberal pension policies later in life, as in Switzerland, intensify pension penalties for typical female work–family life courses of early motherhood and weak labour force attachment. We conclude that life course sensitive social policies should harmonize regulations, which are in effect earlier in life with policies later in life for specific birth cohorts.
Keywords: 330; Retirement; Work-family trajectories; Multichannel sequence analysis; Life course; SHARE data